Proteomic fingerprinting enables quantitative biodiversity assessments of species and ontogenetic stages in Calanus congeners (Copepoda, Crustacea) from the Arctic Ocean. (29th September 2022) - Rossel, Sven; Kaiser, Patricia; Bode‐Dalby, Maya; Renz, Jasmin; Laakmann, Silke; Auel, Holger; Hagen, Wilhelm; Arbizu, Pedro Martínez; Peters, Janna
Abstract: Species identification is pivotal in biodiversity assessments and proteomic fingerprinting by MALDI‐TOF mass spectrometry has already been shown to reliably identify calanoid copepods to species level. However, MALDI‐TOF data may contain more information beyond mere species identification. In this study, we investigated different ontogenetic stages (copepodids C1–C6 females) of three co‐occurring Calanus species from the Arctic Fram Strait, which cannot be identified to species level based on morphological characters alone. Differentiation of the three species based on mass spectrometry data was without any error. In addition, a clear stage‐specific signal was detected in all species, supported by clustering approaches as well as machine learning using Random Forest. More complex mass spectra in later ontogenetic stages as well as relative intensities of certain mass peaks were found as the main drivers of stage distinction in these species. Through a dilution series, we were able to show that this did not result from the higher amount of biomass that was used in tissue processing of the larger stages. Finally, the data were tested in a simulation for application in a real biodiversity assessment by using Random Forest for stage classification of specimens absent from the training data. This resulted in a successful stage‐identification rate of almost 90%, making proteomic fingerprinting a promising tool to investigate polewards shifts of Atlantic Calanus species and, in general, to assess stage compositions in biodiversity assessments of Calanoida, which can be notoriously difficult using conventional identification methods.